Neurosurgery for intracranial meningioma in patients aged more than 80 years: benefits and rationale. (4th July 2021) - Joubert, Christophe; Sellier, Aurore; Sahuc, Pauline; Beucler, Nathan; Desse, Nicolas; Bernard, Cedric; Cungi, Pierre-Julien; Dagain, Arnaud
Abstract: Background: Elderly patients with symptomatic benign intracranial tumours such as meningioma pose particular problems in decision making. We report on the outcome, morbidity and mortality in patients aged over 80 years after undergoing cranial surgery for meningiomas. Methods: In this retrospective study, 37 patients aged more than 80 years underwent surgery at our neurosurgery department. The Karnofsky Performance Scale (KPS) was used to assess functional status. The American Society of Anesthesiologists (ASA) classification system, the Geriatric Scoring System, the Clinical-Radiological Grading System and the Sex, Karnofsky, ASA, Location and Edema score were used to define clinical status and tumour characteristics. The Charlson Comorbidity Index and Clavien–Dindo classification scores reflected therapeutic morbidity. Results: Preoperative KPS scores were generally higher than 60 ( n  = 32). Of the 37 patients, 24 (64.8%) were in ASA class I or II, and 27 (73.0%) had one or more comorbidities. The median length of follow-up was 80.0 months (range: 1–96 months). The 1-year mortality rate was 2.7% ( n  = 1). Tumour control was achieved in 33 patients. At discharge, KPS scores were improved in 21 patients (with an average gain of +18.1 ± 8.7), stable in 10 patients and poorer in 6 patients. KPS scores improved or were stable in patients with shorter lengths of hospital stay (15.5 ± 17.9 days vs 51.4 ± 25.4 days; p  < 0.01), those with Clavien–Dindo scores lower than 2 ( p  < 0.01) and those with less favourable preoperative KPS scores (69.4 ± 10.9 vs 82.0 ± 11.0; p  = 0.04). Conclusion: Historically, surgery for intracranial meningiomas in patients aged >80 years has been feasible; this series demonstrated decreasing rates of postoperative mortality. Functional benefit should be the main goal of surgery. Perioperative morbidity should be better assessed and predicted because it significantly influences functional outcomes.